2016
DOI: 10.1093/aje/kww085
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Rate and Severity of Exacerbations in Chronic Obstructive Pulmonary Disease: An Application of a Joint Frailty-Logistic Model

Abstract: Exacerbations are a hallmark of chronic obstructive pulmonary disease (COPD). Evidence suggests the presence of substantial between-individual variability (heterogeneity) in exacerbation rates. The question of whether individuals vary in their tendency towards experiencing severe (versus mild) exacerbations, or whether there is an association between exacerbation rate and severity, has not yet been studied. We used data from the MACRO Study, a 1-year randomized trial of the use of azithromycin for prevention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…A previous analysis demonstrated that the pattern of exacerbation occurrence was consistent with a constant hazard over time. 24 Fewer than 4% of individuals died and a previous analysis showed little impact from the competing risk of death on the statistical inference on exacerbation rate. 24 As the treatment is randomized, there is no structural confounding.…”
Section: Application: a Clinical Trial Of Preventive Antibiotic Theramentioning
confidence: 93%
See 1 more Smart Citation
“…A previous analysis demonstrated that the pattern of exacerbation occurrence was consistent with a constant hazard over time. 24 Fewer than 4% of individuals died and a previous analysis showed little impact from the competing risk of death on the statistical inference on exacerbation rate. 24 As the treatment is randomized, there is no structural confounding.…”
Section: Application: a Clinical Trial Of Preventive Antibiotic Theramentioning
confidence: 93%
“…24 Fewer than 4% of individuals died and a previous analysis showed little impact from the competing risk of death on the statistical inference on exacerbation rate. 24 As the treatment is randomized, there is no structural confounding. The possibility of chance confounding (noticeable imbalance of covariates due to randomization 25 ) was ruled out in an exploratory analysis (the standardized mean difference between treatment groups was less than 5% for all covariates).…”
Section: Application: a Clinical Trial Of Preventive Antibiotic Theramentioning
confidence: 93%
“…Empirical evidence supports the presence of such heterogeneity(33). The extent of such heterogeneity was based on our previous work using data from the MACRO study(34). This heterogeneity was modeled through individual-specific (random-effect) intercepts for log-hazard of exacerbation rate and log-odds of exacerbation severity ( Table 1 )(34).…”
Section: Methodsmentioning
confidence: 99%
“…It is increasingly recognized that COPD is a heterogeneous disease. Individuals can vary markedly in their rate of lung function decline 13 and frequency of exacerbations 14,15 over the course of their disease. For example, COPD patients in the Lung Health Study had an annual rate of change in FEV 1 that ranged from rapidly declining to modestly increasing (95% CI −83 mL/yr to +15 mL/yr).…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, the annual rate of exacerbations observed in the MACRO clinical trial varied from 0.47 to 4.22. 15 Quantifying this variation at an individual level is critical to enabling precise risk factor and disease management. 16…”
Section: Introductionmentioning
confidence: 99%